Gender, Motivation, and Self-Selection into Teaching - Francesca Barigozzi; Jaai Parasnis; Massimiliano Tani (Institute of Labor Economics (IZA), 2022)
This paper investigates the role of intrinsic and extrinsic motivation in choosing a teaching career using data from the Household Income and Labour Dynamics in Australia. We find that the opportunity costs of becoming a teacher vary by gender: women enjoy a small wage premium, whilst males suffer a large wage penalty. We also find that non-monetary aspects and job amenities (such as motivation for the job, job security, and work/family life balance) have a different influence on teaching careers by gender, which can influence the sorting of male and female teachers across government and private schools. Notwithstanding evidence of positive selection into teaching in terms of cognitive ability and motivation for the job, the asymmetries in opportunity costs and non-monetary aspects reveal that introducing differentiated contracts tailored to gender preferences may influence teachers' recruitment by gender. However, we caution that such prospective initiatives need to balance the trade-off between attracting talented and motivated individuals into teaching and promoting gender equality, which arises from the data.
Keywords: I21; J16; J24; J31; M52; 330; decomposition; Australia; incentives; teacher